Human Immune Responses to Dengue Virus Infection: Lessons Learned from Prospective Cohort Studies - Endy, Timothy P. (Frontiers in Immunology, 2014)
Dengue virus (DENV) continues to spread globally and is a major cause of morbidity and mortality. Currently there is no antiviral treatment to diminish severe illness or a vaccine to induce protection from infection. An effective dengue vaccine that protects against all four DENV serotypes is a high priority for endemic countries and several candidates are in development by various United States Federal Agencies and private pharmaceutical companies. Challenges faced by dengue vaccine developers include creating tetravalent formulations that provide tetravalent protection, the lack of a correlate of protective immunity, a changing viral landscape as DENV evolves, and a complex viral-host pathogenesis that can result in a spectrum of illness from subclinical infection to severe hemorrhagic fever. There have been a number of long-term prospective studies on DENV transmission and dengue severity that have provided invaluable information on DENV epidemiology and pathogenesis of this disease. In this section we will review the critical lessons learned from these studies and their application for dengue vaccine development.